[22] Urinary colonisation in patients with JJ catheters - Amine Saouli (Taylor & Francis Group, 2018)
Objective: To evaluate the prevalence of urinary colonisation in patients with JJ catheters and to define the risk factors associated with these colonisations, as urinary colonisation in patients with JJ catheters plays a key role in the physiopathology of urinary tract infections. Methods: This was a monocentric prospective study between January 2013 and April 2017. In all, 145 JJ ureteric catheters in 120 patients, 25 of which had bilateral probes, were examined. The bacteriological profile of the urine of our patients was followed by the completion of an initial cytobacteriological examination of urine and another at the time of removal of the JJ catheter. The comparison of the means was performed using the Student’s test and the Mann–Whitney test for continuous variables and by the chi-square test and Fisher’s test for qualitative variables. The threshold for statistical significance was set at P < 0.05. Results: The rate of colonised JJ probes was 35.8% (43/145). The urinary colonisation rate was 31.7%. The rate of urinary colonisation in patients with colonised probes was 71.1%, compared to 9.1% for non-colonised probes. Of the identified pathogens, Escherichia coli was found in 38.1% of the colonised probes; Klebsiella pneumoniae was second (19.1%), followed by Enterococcus faecalis (16.6%). The same bacteria isolated in the JJ probes were found in the urine. Diabetes mellitus (P = 0.001), emergency JJ placement (P = 0.02), and JJ implantation time (P = 0.01), were risk factors for urinary colonisation in patients with JJ probes. Conclusion: The prevalence of urinary colonisation in patients with JJ catheters was 31.7%. Diabetes mellitus, prolonged JJ implantation, and emergency JJ placement were associated with a higher risk of urinary colonisation.